PP30 Differences in care? The experience of maternity care for women of different ethnicities. (2nd September 2014) - Henderson, J; Redshaw, M
Abstract : Background: According to the Office for National Statistics, approximately a quarter of women giving birth in England and Wales are from minority ethnic groups. Previous work has indicated that these women have poorer pregnancy outcomes than White women and poorer experience of maternity care, sometimes encountering stereotyping and racism. The aims of this study were to examine service use and perceptions of care in ethnic minority women from different groups compared to White women. Methods: Secondary analysis of data from two national surveys of women in 2010 was undertaken. The questionnaires asked about women's experience of care during pregnancy, labour and birth, and the postnatal period, as well as demographic factors. Ethnicity was grouped into eight categories: White, Mixed, Indian, Pakistani, Bangladeshi, Black Caribbean, Black African, and Other ethnicity. Results: A total of 24, 319 women completed one survey; the other, more in depth survey, had 5333 respondents. Compared to White women, women from minority ethnic groups were more likely to be younger, multiparous and without a partner. They tended to access antenatal care later in pregnancy, have fewer antenatal checks, fewer ultrasound scans and less screening. They were less likely to receive pain relief in labour and, Black African women in particular, were more likely to deliver by emergency caesarean section. Postnatally, women from minority ethnic groups had longer lengths of hospital stay and were more likely to breastfeed but they had fewer home visits from midwives. Throughout their maternity care, women from minority ethnic groups were less likely to feel spoken to so they could understand, to be treated with kindness, to be sufficiently involved in decisions and to have confidence and trust in the staff. Much of this was related to recency of migration. For example, women who had arrived in the UK more than 10 years ago were less likely to breastfeed than those arrived more recently. Similarly, recent migrants were more likely to consider that they were not spoken to so that they could understand or treated with kindness by staff. Conclusion: Women in all minority ethnic groups had a poorer experience of maternity services than White women. That this was still the case following publication of a number of national policy documents and local initiatives is a cause for concern.